Voices and dialogues. Gender representations in women’s radio programs during the Franco ́s dictatorship (1939-1959) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2020)
Radio had a close relationship with women since its inception. The entrance into the receiver’s home imbriced time and domestic space with radio broadcasts, not in vain, the female audience became its main standard. Once the “new State” was established, the Franco dictatorship reconfigured the function of radio as a pedagogical and propaganda device. The diffusive capacity and communicative power of the waves served the purposes of the regime that sought to cement the doctrines of national Catholicism. Radio talk practices built a system of gender and cultural representations that sought to root the ideal of femininity of the “perfect housewife”. To this end, radio was a map of symbols and meanings that, on a daily and repeated basis, was modifying the female social imaginary and its social practices. In this article, we will aim to reflect what this series of discursive mechanisms consisted of and what role radio played as the builder of a representation system. To do this, we will analyze the scripts of the women’s programs broadcast on the private station Radio Madrid during the chronology that we address.
Keywords: radio; francoist dictatorship; women's history; gender history; representations